Smoking cessation support for pregnant women: role of mobile technology - Heminger CL; Schindler-Ruwisch JM; Abroms LC (Dove Medical Press, 2016)
Christina L Heminger, Jennifer M Schindler-Ruwisch, Lorien C AbromsDepartment of Prevention and Community Health, Milken Institute School of Public Health, The George Washington University, Washington, DC, USA Background: Smoking during pregnancy has deleterious health effects for the fetus and mother. Given the high risks associated with smoking in pregnancy, smoking cessation programs that are designed specifically for pregnant smokers are needed. This paper summarizes the current landscape of mHealth cessation programs aimed at pregnant smokers and where available reviews evidence to support their use. Methods: A search strategy was conducted in June–August 2015 to identify mHealth programs with at least one component or activity that was explicitly directed at smoking cessation assistance for pregnant women. The search for text messaging programs and applications included keyword searches within public health and medical databases of peer-reviewed literature, Google Play/iTunes stores, and gray literature via Google. Results: Five unique short message service programs and two mobile applications were identified and reviewed. Little evidence was identified to support their use. Common tools and features identified included the ability to set your quit date, ability to track smoking status, ability to get help during cravings, referral to quitline, and tailored content for the individual participant. The theoretical approach utilized was varied, and approximately half of the programs included pregnancy-related content, in addition to cessation content. With one exception, the mHealth programs identified were found to have low enrollment. Conclusion: Globally, there are a handful of applications and text-based mHealth programs available for pregnant smokers. Future studies are needed that examine the efficacy of such programs, as well as strategies to best promote enrollment. Keywords: mHealth, smoking cessation, pregnancy, text messaging, mobile applications